Titanium dioxide nanoparticles: Recent progress in antimicrobial applications - Younis, Almotasem Bellah; Haddad, Yazan; Kosaristanova, Ludmila; Smerkova, Kristyna (Wiley interdisciplinary reviews. Nanomedicine and nanobiotechnology, 2023)
For decades, the antimicrobial applications of nanoparticles (NPs) have attracted the attention of scientists as a strategy for controlling the ever-increasing threat of multidrug-resistant microorganisms. The photo-induced antimicrobial properties of titanium dioxide (TiO2 ) NPs by ultraviolet (UV) light are well known. This review elaborates on the modern methods and antimicrobial mechanisms of TiO2 NPs and their modifications to better understand and utilize their potential in various biomedical applications. Additional compounds can be grafted onto TiO2 nanomaterial, leading to hybrid metallic or non-metallic materials. To improve the antimicrobial properties, many approaches involving TiO2 have been tested. The results of selected studies from the past few years covering the most recent trends in this field are discussed in this review. There is extensive evidence to show that TiO2 NPs can exhibit certain antimicrobial features with disputable roles of UV light. Hence, they are effective in treating bacterial infections, although the majority of these conclusions came from in vitro studies and in the presence of some additional nanomaterials. The methods of evaluation varied depending on the nature of the research while researchers incorporated different techniques, including determining the minimum inhibitory concentration, cell count, and using disk and well diffusion methods, with a noticeable indication that cell count was the most and dominant criterion used to evaluate the antimicrobial activity. This article is categorized under: Nanotechnology Approaches to Biology > Nanoscale Systems in Biology Therapeutic Approaches and Drug Discovery > Emerging Technologies Therapeutic Approaches and Drug Discovery > Nanomedicine for Infectious Disease.
Keywords: nanostruktury; drug resistance; nanomaterial; Nanoparticles; Anti-Infective Agents; microorganisms; Titanium; TiO2; antiinfekční látky; Nanostructures; antibacterial; bacteria; kovové nanočástice; Metal Nanoparticles; titan; nanočástice